PHYTOPLANKTON COMPOSITION OF MARICULTURE AREA IN SUNGAI UDANG, PENANG, MALAYSIA, THE NORTHERN STRAIT OF MALACCA - Mohd Razali, Roziawati; A. Rahim, Masazurah; Ku Yaacob, Ku Kassim (Malaysian Journal of Science, 2021)
A study was conducted in the marine finfish cage culture area in Sungai Udang, Penang, at the northern part of the Malacca Straits to examine the phytoplankton composition and abundance especially for potentially harmful phytoplankton. Monthly sampling were taken from March 2016 to January 2017 at nine sampling stations. Physio-chemical parameters of surface seawater such as pH, dissolved oxygen, temperature, salinity, total suspended solids, and nutrients (nitrate, nitrite, ammonium, phosphate and silicate) were also measured. A total of 54 phytoplankton taxa were recorded, with 37 genera belonged to diatoms, 15 of dinoflagellates, and 2 of cyanobacteria. The composition of phytoplankton was dominated by diatoms (>85%) at all sampling stations throughout the sampling period. The phytoplankton abundance ranged between 2.6×103 cells L-1 and 5.8×106 cells L-1. The potentially harmful toxic phytoplankton observed throughout the sampling period are dinoflagellates Alexandrium spp., Prorocentrum micans and Dinophysis caudata and diatoms, Pseudo-nitzchia spp but in low cell density. A total of six bloom-forming phytoplankton that can potentially trigger mass mortality of cultured fish such as Akashiwo sanguinea, Chaetoceros spp., Ceratium furca, Ceratium fusus, Margalefidinium spp. and Karlodinium spp. recorded at this area were relatively low in cell densities. Furthermore, no fish kill incident was reported in the area from blooms of phytoplankton during the period of study. Even though potentially harmful phytoplankton present were in low densities, they may pose significant risks to aquaculture activity if there is a sudden bloom. Hence, a monitoring program should be implemented to provide early warning of harmful algae blooms and safeguard the aquaculture industry in Sungai Udang, Penang.